Non-parametric analysis of yield risk in Lithuanian crop farming - Baležentis, Tomas; Štreimikienė, Dalia; Melnikienė, Rasa; Yu, Zhiqian (Journal of Business Economics and Management, 2017)
Socioeconomic development requires meeting the goals of food security. Yield risk constitutes an important factor of farming business viability. As the Central and Eastern European countries have been affected by both economic and environmental transformations, there is a need to develop a robust methodology for assessment of yield risks in order to propose convincing guidelines for both farmers and government institutions in regards to risk management and viability of agricultural business in general. This paper attempts to devise non-parametric measures of yield risk for Lithuanian crop farming. The research covers the period of 2000–2015. County-level data from Statistics Lithuania are employed for the analysis. The non-parametric analysis of yield risk relies on information diffusion theory and linear moving average. The results indicate that there exist differences in yield trends, yield loss rates and yield risk among crops and regions. Maize, buckwheat and winter rape exhibited the highest yield risk. These results shed light on the extent of yield risks underlying crop farming in Lithuania and, to a certain extent, can be contrasted to situation in Central and Eastern European countries. Indeed, the obtained results can be applied in decision making at different levels of management.